Total mixed ration for dairy cows - Chaudhari, Alkesh; Obero, P. S. (Indian Farming, 2018)
Such type of feeding system besides causing decrease in production performance can also deteriorate reproductive health of the dairy cows. There is need to give serious thought for switching from traditional feeding system to total mixed ration feeding system for improving milk production and reducing metabolic diseases in dairy cows as well for reducing cost of milk production in our country.